The musical playground : global tradition and change in children's songs and games - Marsh, Kathryn (Kathryn McLeod) (Oxford University Press, 2008)
Section 1: Children's Musical Play and Creativity: Adult Views. 1. Conceptions of Children's Musical Play. 2. Children's Musical Creativity and Oral Transmission. Section 2: Into the Field. 3. Investigating Musical Play: Ethics and Pragmatics. 4. The Playing Fields. Section 3: Transmission Processes in the Playground. 5. The Influence of Social Grouping. 6. Teaching and Learning in the Playground. 7. Changing the Tradition. Section 4: Composition in Performance. 8. Composition in the Playground. 9. Variations on a theme: Sar Macka Dora. 10. Style and Cultural Idiosyncracy. Section 5: Conclusio.